MANAJEMEN RUANG TERBUKA HIJAU di KOTA SEMARANG - Ferdinand Harianja; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The problems encountered in Open Green Space Management in the city of Semarang is the absence of good planning, organizing and mobilization in the field of human resources. This study aims to determine the management of open green space of Semarang City which includes planning, organizing, mobilizing and supervision as well as knowing the obstacles faced by the Office of Housing and Settlement Area of Semarang City in managing open green space. This research use desciptive qualitative approach. Data collection techniques used were interview, observation and document study. The results showed that Semarang open green space management is not optimal yet. This is because there is still a problem in planning where the shortage of expert experts lanskape so that without a lanskape expert of park development will be less adequate, organizing where the placement of employees is still less appropriate with the educational background and positions are diemban and mobilization that is the potential development of subordinates are still rare do. Recommendations that can be done to improve Poen Green Space Management in Semarang City is to plan by looking for experts of landscape planning of garden development, organizing by improving coordination with local government related to human resource problem and recruiting employees in accordance with competence, The development of potential employees through the provision of educational opportunities.